2021
DOI: 10.5194/acp-2021-961
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An assessment of tropopause characteristics of the ERA5 and ERA-Interim meteorological reanalyses

Abstract: Abstract. The tropopause layer plays a key role in manifold processes in atmospheric chemistry and physics. Here we compare the representation and characteristics of the lapse rate tropopause according to the definition of the World Meteorological Organization (WMO) as estimated from European Centre for Medium-Range Weather Forecasts (ECMWF) reanalysis data. Our study is based on ten-year records (2009 to 2018) of ECMWF's state-of-the-art reanalysis ERA5 and its predecessor ERA-Interim. The intercomparison rev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…1) compared to Zou et al (2020, Fig.3) using ERA-interim tropopauses. The statistical analysis of ERA-interim and ERA5 tropopause heights shows that depending on season and hemisphere, the mean midlatitude tropopause in ERA5 is between 100 m lower to 80 m higher than the ERA-interim tropopause (Hoffmann and Spang, 2021, Fig6a, at 45 • ). Hence, the ERA5 tropopause at midlatitudes remains the approximately same, lowering of the threshold distance to the tropopause results in more cloud detections, as one would expect.…”
Section: Regional Analysesmentioning
confidence: 97%
“…1) compared to Zou et al (2020, Fig.3) using ERA-interim tropopauses. The statistical analysis of ERA-interim and ERA5 tropopause heights shows that depending on season and hemisphere, the mean midlatitude tropopause in ERA5 is between 100 m lower to 80 m higher than the ERA-interim tropopause (Hoffmann and Spang, 2021, Fig6a, at 45 • ). Hence, the ERA5 tropopause at midlatitudes remains the approximately same, lowering of the threshold distance to the tropopause results in more cloud detections, as one would expect.…”
Section: Regional Analysesmentioning
confidence: 97%
“…We illustrate the tropopause layer with the top and bottom contours given by the cold point definition and World Meteorological Organization (WMO) lapse‐rate definition, respectively. The WMO tropopause is the lowest level where the absolute value of the temperature lapse rate decreases to 2K/km, or less, with the average lapse rate between this level and all higher levels within 2 km not exceeding 2K/km (Hoffmann & Spang, 2021). The “dynamic” tropopause, a potential vorticity contour of +3.5 PVU, is also shown.…”
Section: What Plume Temperature At the Boundary‐layer Top Enables Dry...mentioning
confidence: 99%
“…The “dynamic” tropopause, a potential vorticity contour of +3.5 PVU, is also shown. The zonal and time average tropopause contours are computed from the ERA5 tropopause data set (Hoffmann & Spang, 2021).…”
Section: What Plume Temperature At the Boundary‐layer Top Enables Dry...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, because folding is a meso-to synoptic-scale process, capturing fold morphology and fold-related turbulent STT processes requires resolutions <50 km (Knowland et al, 2017;Buker et al, 2005;Spreitzer et al, 2019). Consequently, the frequency of "double-tropopause" structures (of which folding is one type) is significantly higher in high-resolution ERA5 versus ERA-Interim (Hoffmann & Spang, 2022). High-resolution observational evidence, although sparse and localized, has suggested that atmospheric transport structures are horizontally and vertically filamentary, characterized by thin, diffusion-resistant layers (Danielsen, 1959;Appenzeller & Davies, 1992;Appenzeller et al, 1996;Newell et al, 1996Newell et al, , 1999Trickl et al, 2010Trickl et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%